2008
DOI: 10.2135/cropsci2008.03.0134
|View full text |Cite
|
Sign up to set email alerts
|

The Fate and Transport of Phosphorus in Turfgrass Ecosystems

Abstract: All rights reserved. No part of this periodical may be reproduced or transmitted in any form or by any means, electronic or mechanical, including photocopying, recording, or any information storage and retrieval system, without permission in writing from the publisher. Permission for printing and for reprinting the material contained herein has been obtained by the publisher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 78 publications
4
68
1
Order By: Relevance
“…Laboski et al (2006) Dane County soil P concentrations Bennett et al (1999) Feed supplements for dairy cattle Average feed consumed per cow per day in South Central WI Powell et al (2002) Percent of P in feed that is homegrown versus imported Powell et al (2002) Number of cattle in Dane County USDA-NASS (2009a) Herd structure of cattle South Central WI Powell et al (2002) Fertilizer for urban lawn Urban land area in the watershed Bennett et al (1999) Percent of urban area that is lawn Bannerman et al (1993) Recommended fertilization rates Soldat and Petrovic (2008) Atmospheric deposition Dry deposition Lathrop (1979) Wet deposition Lathrop (1979) Outputs (2000) % P in milk and eggs Lorimor et al (2000) Hydrologic export to Lake Mendota Hydrologic export to Lake Mendota Lathrop et al (1998) Phosphorus management scenarios 243 deposition. Fertilizer for urban lawns was calculated based on the percent of turf-covered urban area in the watershed (Bennett et al 1999;Bannerman et al 1993) and the recommended fertilization rates (Soldat and Petrovic 2008). Mass of phosphorus imported in animal feed supplements was estimated using data particular to south-central Wisconsin dairy herds (Powell et al 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboski et al (2006) Dane County soil P concentrations Bennett et al (1999) Feed supplements for dairy cattle Average feed consumed per cow per day in South Central WI Powell et al (2002) Percent of P in feed that is homegrown versus imported Powell et al (2002) Number of cattle in Dane County USDA-NASS (2009a) Herd structure of cattle South Central WI Powell et al (2002) Fertilizer for urban lawn Urban land area in the watershed Bennett et al (1999) Percent of urban area that is lawn Bannerman et al (1993) Recommended fertilization rates Soldat and Petrovic (2008) Atmospheric deposition Dry deposition Lathrop (1979) Wet deposition Lathrop (1979) Outputs (2000) % P in milk and eggs Lorimor et al (2000) Hydrologic export to Lake Mendota Hydrologic export to Lake Mendota Lathrop et al (1998) Phosphorus management scenarios 243 deposition. Fertilizer for urban lawns was calculated based on the percent of turf-covered urban area in the watershed (Bennett et al 1999;Bannerman et al 1993) and the recommended fertilization rates (Soldat and Petrovic 2008). Mass of phosphorus imported in animal feed supplements was estimated using data particular to south-central Wisconsin dairy herds (Powell et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…We therefore used zero as our minimum estimate for urban P fertilizer use. Maximum estimates assumed that 20% of the 200,000 lawns in the watershed were fertilized twice a year which is a baseline recommended rate of application (Soldat and Petrovic 2008). The most likely estimate was an average of the maximum and minimum estimates.…”
Section: Urban Fertilizermentioning
confidence: 99%
“…Time to runoff for grass generally ranges from 2 to 15 min [26] [27]. Sediment loss from grass can range from 10 to 180 kg¡ha −1 over 35 min [26], or from 0.1 to 104 kg¡ha −1 per event of 12 to 30 min duration [28]. In our study, the soil was initially-dry and slopes were less-steep than for studies in the literature; therefore, we showed increased time to runoff compared with literature studies.…”
Section: Second Rainfall Simulationmentioning
confidence: 99%
“…Obviously, increasing the intensity of management is a strategy for golf course to attract more visitors under this condition. The intensively managed turfgrass areas are subjected to routine applications of fertilizer and agrochemicals to support plant growth and http://dx.doi.org/10.1016/j.ecolind.2015.11.056 1470-160X/Š 2015 Published by Elsevier Ltd. maintain esthetic quality, including tees and greens, and fairways (Soldat and Petrovic, 2008). Meanwhile, the negative environmental effects caused by intensive managements will increase, such as nonpoint-source pollution (Haith, 2010), large consumption of water (Diaz et al, 2007) and greenhouse gas emissions (Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%